Cybersecurity Policy Research in the Social Sciences: A Systematic Literature Review and Bibliometric Analysis - Refa Andrean Tri P; Ismi Dwi Astuti Nurhaeni; Faizatul Ansoriyah (Smart Society, 2026)
The global digital transformation has positioned cybersecurity policy as a strategic issue within the social sciences rather than merely a technical concern. Although cybersecurity has been widely examined in technical, engineering, and information systems domains, studies that systematically map cybersecurity policy research from a social science perspective remain limited and fragmented across governance, regulatory, institutional, and socio-political dimensions. Therefore, a comprehensive synthesis is needed to better understand the development, intellectual structure, and future directions of cybersecurity policy scholarship within the social sciences. This study aims to map the development of cybersecurity policy research, identify publication patterns based on countries, institutions, sources, and publication types, and synthesize the key determinants and social dimensions associated with cybersecurity policy. The study employs a Systematic Literature Review and bibliometric analysis of 70 Scopus-indexed articles published up to March 17, 2026. The findings reveal a substantial increase in cybersecurity policy research over the past decade, particularly in studies related to governance, regulation, and geopolitical issues, reflecting a growing multidisciplinary orientation. The thematic synthesis and literature analysis identify five key determinants of cybersecurity policy and several social, political, and economic dimensions frequently associated with cybersecurity governance. These findings are integrated into a conceptual model developed from literature synthesis and bibliometric mapping to illustrate the relationships among the identified determinants and associated dimensions. This study contributes to enriching the cybersecurity policy literature from a social science perspective and provides directions for future research and policy development.